Frecuencia de la identificación de los genes blaKPC y blaOXA-48 en cultivos de E.coli y K. pneumoniae de origen intrahospitalario que fenotípicamente pertenecen al grupo de las serincarbapenemasas; Enero – Marzo, Trujillo 2018. - Pérez Muguerza, María Katherine (2018)
The resistence to the antibiotics constitutes one of the most important problems of the public health in the whole world._x000D_ The enterobacterias producer of the carbapenemases represents the greatest threat. The carbapenemasas are potent ensymes that inactive the carbapenem antibiotics and in general to all the betalactam antibiotics._x000D_ This research aimed to determine the frecuency of blaKPC and blaOXA-48 in 66 growth bacterial cultures of Escherichia coli and 34 growth bacterial cultures of Klebsiella pneumonia provided by the Belen Hospital of Trujillo during the months of January to March of 2018. For this, it was determined betalactamases ensymes type of extended-spectrum BLEE and by identifying the carbapenemases ensyme type through the Hodge Test modified the total of population under the standards of the CLSI 2015.The synergy of disk tet with APB was realized to the positive growth bacterial cultures to the Hodge Test modified by the detection of the carbapenemases producers type A. It was determined through the PCR conventional the presence of the blaKPC to the positive growth bacterial cultures to the synergy test with APB and the presence of blaOXA-48 gene to the negative growth bacterial cultures of the same test. The blaKPC gene only was in the Klebsiella pneumoniae growth bacterial cultures (2.9%). It was not detected the presence of the blaOXA-48 gene in any of the evaluated growth bacterial cultures._x000D_ Key